Perancangan Aplikasi Pemesanan Tiket Wisata di Kecamatan Donorojo Menggunakan Metode Payment Gateway - Hadi Wiyono; Muhammad Fachrie (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Currently, the process of ordering tourist tickets is still done manually, especially in the Donorojo area, namely by visiting a travel agent or contacting the relevant party by telephone to order tickets. This process tends to take a long time, especially if users must queue to place an order. In addition, information regarding ticket prices and available schedules is not always easily accessible to users. The impact of this problem is confusion and errors in ordering tickets, as well as the buildup of queues at counters which causes congestion. To overcome this problem, we developed a tourist ticket booking application in Donorojo sub-district by implementing payment gateway methods including Flutter as a mobile application development framework and Firebase as a database management system that allows users to order tickets online, find out available tourist destination information and prices. and the schedule of tickets offered. The solution step taken is to collect and analyze data regarding popular tourist destinations, as well as implementing an online payment feature in the application. The interim results we have obtained are applications that are able to provide information about available tourist destinations, as well as provide convenience in the payment process and increase transaction security by using this payment gateway. Users can choose the desired destination, select the date and number of tickets needed, and make payment via the application. After payment is complete, the application will issue an electronic ticket which can be shown upon arrival at the tourist destination.